1991
DOI: 10.1210/jcem-72-3-602
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Osteopenia in Adolescent Girls with Anorexia Nervosa*

Abstract: Osteopenia is a frequent complication of anorexia nervosa (AN). To determine whether the deficit in bone mineral changes during the course of this illness, we studied 15 adolescent patients prospectively for 12-16 months using dual photon absorptiometry of the spine and whole body. At follow-up, mean weight, height, and body mass index (BMI) had increased significantly, although 6 girls had further weight loss or minimal gain (less than 1.2 kg). Spontaneous menses occurred in 2 girls, and 3 others were given e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
295
6
18

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 347 publications
(333 citation statements)
references
References 13 publications
14
295
6
18
Order By: Relevance
“…Weight recovery has been shown to increase whole-body bone density, even before the return of menses. 43 In this same study, however, lumbar bone density remained significantly reduced and subsequent weight loss was associated with further decreases in bone density. Despite their gains in BMD, 8 patients had osteopenia of the spine or whole body, or both.…”
Section: Osteoporosismentioning
confidence: 67%
See 4 more Smart Citations
“…Weight recovery has been shown to increase whole-body bone density, even before the return of menses. 43 In this same study, however, lumbar bone density remained significantly reduced and subsequent weight loss was associated with further decreases in bone density. Despite their gains in BMD, 8 patients had osteopenia of the spine or whole body, or both.…”
Section: Osteoporosismentioning
confidence: 67%
“…40,41 Studies have shown that adolescents with AN have significantly reduced bone mass compared with agematched 41 and bone age-matched controls. 42 In one study, 41 the lumbar bone density of two-thirds of adolescents with AN was more than 2 SD lower than the normal values for their age. Of note, the changes in bone density occurred very early in the course of the illness, with one half of these adolescent girls having had a diagnosis of AN for <1 year.…”
Section: Osteoporosismentioning
confidence: 99%
See 3 more Smart Citations